PENGARUH NET PROFIT MARGIN, EARNING PER SHARE, DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PERUSAHAAN RETAEL TRADE YANG TERDAFTAR DI BURSA EFEK DI INDONESIA PERIODE 2015-2017. - Viqi Hendro Fahtoni; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to test and analyze the effect of Net Profit Margin, Earning Per Share and Return On Equity on Ritael Trade companies that are listed on the Indonesia Stock Exchange during the 2015-2017 Period. The population that is the object of this research are all Ritael Trade Companies Registered on the Indonesia Stock Exchange during the period 2015-2017, namely 25 companies. The sampling technique used a purposive sampling method, so that it obtained 14 companies. Data analysis in this study uses SPSS version 16. The data testing techniques used in this study include normality test, classic assumption test and multiple linear regression analysis, and testing the research hypothesis.The results of the analysis show that Net Profit Margin (NPM) and Return On Equity (ROE) have a negative but not significant effect on stock prices. While Earning Per Share (EPS) partially has a positive and significant effect on stock prices. Keywords: Net Profit Margin, Earning Per Share, and Return On Equity.